Penerapan Hidroponik Pasang Surut (Ebb-Flow) dengan Teknologi Bell-Siphon untuk Produksi Tanaman Selada yang Ekonomis di Kelurahan Bajubodoa, Kabupaten Maros - Nur Annisa; Tri Indriani; Irfan Irfan; Ahmad Anugrah Wahidin; Muhammad Kadir (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Hydroponics as an urban farming model is very meaningful to the community, including the Inkiya Farm business in Bajubodoa village, Maros district. There are several obstacles in the production of lettuce vegetables in hydroponics that are run so that they experience fluctuations, by natural disturbances causing plant damage and even crop failure (wilting or dying), limited space, drought resistance and less than optimal growth which is generally experienced because 100% using the NFT system. The implementation of Bell-Siphon on Ebb Flow system hydroponic technology is an alternative solution that is cheaper, environmentally friendly, space saving and more optimal plant production. The Bell-Siphon unit driving the tidal system is simply assembled, placed in a hydroponic container. This science and technology application activity results in additional knowledge for partners on how to build or assemble a Tidal System with Bell Siphon to increase the amount of production, reduce the risk of crop failure, and the potential for better production of lettuce plants. The activity resulted in at least 6 units of Ebb-Flow hydroponics in containers (tubs) with various media, installation and training for women members of the partners. Sustainability of implementation is expected at Partners as well as at the household scale in each member who has received training.